"It's a three-way ring": E-hailing platforms, drivers and riders reshaping Accra's mobility landscape. Issue 3 (September 2022) - Pasquali, Paola; Commenges, Hadrien; Louail, Thomas
Highlights: Platforms' competition slashed ride prices but increased drivers' bargaining power. E-hailing platforms vitally depend on local investments by car owners and drivers. Urban mobility actors are part of a shifting system where each depends on others. Abstract: E-hailing platforms are currently booming in many global South cities, often circumventing local transport regulations thanks to their status of technology company. Ghana's capital Accra, where demand for reliable transportation is huge, is a typical example for such phenomenon. We present the results of an investigation intended to provide a multi-faceted account of how e-hailing platforms have blended into the system of actors who operate urban mobility in Accra. Building upon interviews conducted with a large variety of public and private actors – including e-hailing drivers, taxi drivers, customers, platforms employees, drivers' unions representatives, local investors and regulators – we detail the conditions and consequences of their installation. We focus on three aspects: the adaptation of platforms to the Ghanaian context; the work conditions of e-hailing drivers in Accra and their agency; and the essential role of car owners to sustain the rise of platforms in Global South cities.